Differentiation between Entamoeba histolytica and E. dispar using Enzyme-linked Immunosorbent Assay and Wet Mount Method - A. Kadir, Mohammed; S. Daoud, Ibrahim; Al-Bayati, Zaid (Tikrit Journal of Pharmaceutical Sciences, 2023)
To differentiate between Entamoeba histolytica and E. dispar among patients attended Pediatric, General Hospital and Primary Health Care Centres in Kirkuk City, using Direct wet mount and ELISA techniques.The current study included the examination of (600) stool specimens of patients of different age groups (1-≤60 years) attended Pediatric Hospital, Kirkuk General Hospital, and Primary Health Care Centers in Kirkuk city for the period from 1/8/2008 to 20/4/2009 to search for the prevalence of Entamoeba histolytica and Entamoeba dispar using ELISA. It was found that out of 600 stool specimens examined by wet mount microscopy 25.66 % were infected with E. histolytica / E. dispar. DRG ELISA based antigen detection kit of E. histolytica / E. dispar in stool specimens revealed that 52.12 % were found to be positive of total specimens examined (140 microscopy positive samples and 48 microscopy negative control samples). TechLab ELISA based antigen detection kit specific only for E. histolytica in stool specimens revealed that 6.38 % were positive for E. histolytica, while the remaining negative 93.62 % were considered E. dispar. DRG ELISA based antibody detection of anti-E. histolytica serum IgG revealed seropositivity rate of 36.17 %. The direct stool examination is not capable to differentiate between E. histolytica and E. dispar. TechLab ELISA based antigen detection of E. histolytica is a sensitive and rapid method for detection and differentiation of E. histolytica from E. dispar. DRG ELISA based antibody detection of anti-E. histolytica serum IgG is a helpful mean to detect chronic infection of amebic colitis, asymptomatic cyst carrier patients, and extra-intestinal infection.